Analisis Resepsi Penonton pada Karakter Tokoh dalam Film Teman Tapi Menikah 2 Karya Rako Prijanto pada Mahasiswa Pendidikan Bahasa Indonesia Angkatan 2021 - Muttalib, Abdul; Irmayani, Naim; Nurhashisya, Nurhashisya (UI DDI AGH AD Polewali Mandar, 2023)
This research aims to analyze audience reception, especially Indonesian Language Education students class of 2021, towards the characters in the film